2009
DOI: 10.1097/gme.0b013e318198d6b2
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol levels during the menopausal transition and early postmenopause

Abstract: Aims-Cortisol levels rise among some women during the late stage of the menopausal transition, but we know little about changes in cortisol levels in relation to menopause-related factors (menopausal transition (MT) stage, urinary estrone glucuronide, testosterone, FSH), stress-related factors (epinephrine, norepinephrine, perceived stress), symptoms (hot flashes, mood, memory and sleep), social factors (income adequacy, role burden, social support, employment, parenting, and history of sexual abuse) and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 52 publications
4
42
1
Order By: Relevance
“…The association of cortisol with urinary estrone, FSH, and testosterone in the SMWHS population may suggest that the transition of estrogen production from an ovarian to an adrenal source during the menopausal transition may be marked by a transient period in which levels of both cortisol and HPO axis hormones are elevated. 26 Nonetheless, cortisol does not appear associated with any of the symptom clusters in these analyses.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The association of cortisol with urinary estrone, FSH, and testosterone in the SMWHS population may suggest that the transition of estrogen production from an ovarian to an adrenal source during the menopausal transition may be marked by a transient period in which levels of both cortisol and HPO axis hormones are elevated. 26 Nonetheless, cortisol does not appear associated with any of the symptom clusters in these analyses.…”
Section: Discussionmentioning
confidence: 64%
“…25 Among the SMWHS population, cortisol was positively associated with urinary estrone, epinephrine and norepinephrine levels during the MT stages. 26 …”
mentioning
confidence: 99%
“…Untreated MSCs served as controls. GR siRNA loaded PLGA particles were prepared using a (water-in-oil)-in-water double emulsion solvent evaporation method as previously described [24] . Briefly, GR siRNA (50 μg) was added to 300 μL of a 1% aqueous solution of PVA (water 1 phase).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the effects mediated by GCs may accelerate cell aging and shorten telomere length by increasing oxidative stress and down-regulating the activity of telomerase and antioxidant levels [1720] . Elevated levels of endogenous GCs also contribute to MSC senescence and the development of osteoporosis in aging patients and in those who are postmenopausal and hence estrogen depleted [1224] . Our previously published data have shown that short-term blockage of the effects mediated by the GCs present in fetal bovine serum (FBS) using either the GR antagonist RU486, or the small interfering RNA (siRNA) for GR, significantly improve the proliferative and osteochondral differentiation capabilities of human MSCs [2526] .…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol, a hormone produced in the adrenal glands, and regulated and released by the hypothalamus during times of stress, is often a contributor to this problem. High levels of cortisol contribute to chronic insomnia and feelings of crashing fatigue, but over exposure to cortisol, along with other stress hormone, such as adrenaline, which is also released by the adrenal gland, can put the body at high risk for heart disease, contribute to digestive problem, obesity and even depression [6]. According to WHO, physical activity is defined as any bodily movement produced by skeletal muscles that require energy expenditure.…”
Section: Introductionmentioning
confidence: 99%